1988
DOI: 10.1288/00005537-198802000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Jugular bulb position and shape are unrelated to temporal bone pneumatization

Abstract: The position and shape of the jugular bulb are undependable, and thus can add difficulty to temporal bone surgery. The present study addresses the hypothesis that position and shape of the jugular bulb correlate with the extent of temporal bone pneumatization. Systematic study was done in 25 unilateral cadaver specimens. Pneumatization was determined using both the classic Runström II radiograph, and computed tomography. Jugular bulb shape and position were determined by anatomic dissection and computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 5 publications
2
17
1
Order By: Relevance
“…In an earlier report (Turgut and Tos, 1992), pneumatization of the mastoid bone was claimed as a cause of high JB; however, there are also some other researchers (Orr and Todd, 1988;Aslan et al, 1997) who advocate the idea that there is no relation between the position of the JB and pneumatization. In this study, the JB was found to be higher on the right side; however, no statistically significant differences were found between the COM group and the control group regarding the height of the JB.…”
Section: Discussionmentioning
confidence: 98%
“…In an earlier report (Turgut and Tos, 1992), pneumatization of the mastoid bone was claimed as a cause of high JB; however, there are also some other researchers (Orr and Todd, 1988;Aslan et al, 1997) who advocate the idea that there is no relation between the position of the JB and pneumatization. In this study, the JB was found to be higher on the right side; however, no statistically significant differences were found between the COM group and the control group regarding the height of the JB.…”
Section: Discussionmentioning
confidence: 98%
“…However, Orr et al [14] reported that the dissection determined the distance from the plane of the lateral SSC to the roof of the jugular bulb (2 mm to 15 mm) had a good correlation with the distance from the internal auditory canal to the apex of the JB (1.5 mm to 15.0 mm) [10]. In the presnt study, we measured the SS-LSSC distance as 15.14 ± 1.70 mm in the bilateral HJB group, 15.76 mm in the unilateral HJB group, and 14.38 mm in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…The jugular bulb is known to vary widely in position and dimension and to occasionally cause difficulty in temporal bone surgery [14]. The dehiscent jugular bulb can present a mass lesion in the middle ear and can unexpectedly be a problem during middle ear surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hypotheses have been put forward to explain abnormal developments of the jugular bulb, such as pre vious phlogosis of the middle ear [4], hypoplasia or thrombosis of the contralateral encephalic venous drain age system [1,5], arteriovenous malformations [6], ve nous sinus malformations [7] and low pneumatization of the temporal bone [2], However, recent studies exclude the influence of most of these causes and, in particular, show that there is no relationship between the position of the jugular bulb and the pneumatization of the temporal bone [8,9].…”
Section: Introductionmentioning
confidence: 99%